Formulation and Evaluation of Chewable Tablets from Natural Extracts: A Systematic Literature Review - Nia Yuniarsih; Adam Permana; Nissa, Adinda Khoirun; Adiva Nafila Zulfa; Khoirul Haniatin; Novita Andriyani (Eureka Herba Indonesia, 2023)
Formulation of chewable tablets from extracts of natural ingredients requires special attention in designing preparations that maintain the quality and stability of the active ingredients. The extract must have the desired pharmacological effect and be proven safe to use. This study aimed to carry out a systematic review in order to explore formulations of chewable tablets made from natural ingredients. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the formulation and evaluation of chewable tablets from natural extracts. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. Formulation of chewable tablets from extracts of natural ingredients is an interesting approach in the development of pharmaceutical preparations. Through a selection of appropriate extracts, careful evaluation of stability, and attention to taste and aroma, these chewable tablets can provide significant benefits to patients. However, it is important to carry out careful research and testing to ensure the safety, effectiveness, and quality of these products before they are used in clinical practice.